Hubungan Tingkat Pengetahuan Dan Sikap Tentang Kesehatan Gigi Dengan Perilaku Perawatan Gigi Anak Usia Sekolah Dasar Kelas V Di Sd Negeri 19 Kota Bengkulu Tahun 2024 - Yuniarti, Elza; Darmawansyah, Darmawansyah; Aprianti , Delta (Jurnal Multidisiplin, 2025)
The World Health Organization (WHO) estimated in 2022 that dental and oral diseases affect nearly 3.5 billion people worldwide. Globally, it is estimated that 2 billion people suffer from permanent tooth decay and 514 million children suffer from primary tooth decay. Untreated dental caries (tooth decay) in permanent teeth is the most common health condition. The aim of this study was to determine the relationship between knowledge and attitude levels and dental care behaviour among fifth-grade elementary school children at SD Negeri 19 Kota Bengkulu in 2024. The method used was a quantitative research design employing an analytical cross-sectional study design. Data were collected by distributing questionnaires to 48 respondents at SD Negeri 19 Kota Bengkulu. The sampling technique used purposive sampling. The results of the study revealed that a small proportion of respondents (39.6%) had low levels of knowledge, the majority of respondents (62.5%) had negative attitudes, and a small proportion of respondents (37.5%) exhibited negative dental care behaviour. Statistical tests revealed significant correlations between knowledge (p = 0.012) and attitude (p = 0.021) with dental care behaviour among fifth-grade elementary school children at SD Negeri 19 Kota Bengkulu. There is a relationship between knowledge and attitude levels and dental care behaviour among fifth-grade elementary school children at SD Negeri 19 Kota Bengkulu in 2024. The results of this study are expected to serve as an additional source of information and Communication, Information, and Education (KIE) regarding dental care behaviour among children at SD Negeri 19 Kota Bengkulu in 2024.